Using Mental Modeling to study the management of used cooking oil in Kuala Nerus - Siti Syazuwahanna Binti Mohd ZAMRI; Latifah Binti Abdul GHANI (International Journal of Environmental, Sustainability, and Social Science, 2024)
Recycling of used cooking oil is an effort by collecting, processing and reusing solid waste or materials that have been used for the purpose of environmental conservation. This study was conducted to identify the level of knowledge and awareness of used cooking oil management among the community in the Kuala Nerus district, Terengganu. The study involved 30 respondents in the community, namely traders, used cooking oil wholesalers, households, students and the government. The study used a mixed method, i.e. qualitative and quantitative research using fuzzy cognitive modelling including individual mental model modeling. The results of the study showed that the knowledge of cooking oil waste recycling among the respondents was still at a moderate level. The results of the study found that for the aspect of qualitative analysis, there were four themes that emerged, namely knowledge, awareness, attitude and culture. While descriptive analysis identifies the most dominant relationship strength is the theme of knowledge. The recommendations in this study are necessary to improve the management of used cooking oil in Kuala Nerus through a comprehensive and integrated approach. This study proposes a legal approach, encourages the expansion of this study to a higher level and improves the provision of used cooking oil management infrastructure.